(Un)Covering Hanns Eisler’s Hollywood Songbook - Bohlman, Andrea F.; Bohlman, Philip V. (Danish Yearbook of Musicology, 2008)
Composed during 1942–43, years of Hanns Eisler’s exile from Nazi Germany in Los Angeles, the Hollywood Liederbuch contains 46 settings of poems, largely by fellow exile Bertolt Brecht, but also by other writers, including in two instances by Eisler himself. This article examines the ways in which the intertextuality of the songs, through the multiple sources and changing performances, between the materiality of the song as object and its performativity as subject, transform musical and textual meanings. Hanns Eisler made extensive use of borrowing and covering as a composer, and in the reception history of his work – and of the Hollywood Songbook perhaps more than any other body of works created by Eisler – covers have proliferated in the hands of many performers, in art-song traditions no less than popular music. The authors propose a theory of covering, therefore, that extends its application from popular music to art and composed songs, that is, to the fluid spaces of transmission between oral and written tradition, hence between the ‘active’ and ‘passive voice’ qualities of the ‘cover itself’ and ‘being covered’. The identities generated for the Hollywood Songbook open it to comparison with the fluid canon of American popular song, the ‘Great American Songbook’, and accordingly to the Americanness of Eisler’s compositional work in exile. In conclusion, the authors examine the remarkable vitality of Hanns Eisler in post-Cold War Europe and attribute aspects of reviving the Hollywood Songbook to the renewal that covering its songs inspires.